The impact of obesity on early mortality after coronary artery bypass grafting - Čemerlić-Adjić, Nada; Pavlović, Katica; Jevtić, Marija; Velicki, Radmila; Kostovski, Saša; Velicki, Lazar (Vojnosanitetski pregled, 2013)
Background/Aim. It had been suggested that elevated body mass index (BMI) is a beneficial and preventive factor when it comes to the outcome for patients undergoing coronary artery bypass grafting (CABG). At the same time, obesity is strongly associated with coronary artery disease development. The aim of this study was to determine the significance of the obesity paradox in patients referred for CABG and to examine if a relationship exists between obesity and early coronary surgery outcome. Methods. This study comparised 791 patients who had undergone isolated CABG over one year period (year 2010). The average age of patients was 62.33 ± 8.12 years and involved 568 (71.8%) male and 223 (28.2%) female patients, while the mean logistic EuroSCORE was 3.42%. The patients were categorized into three distinct groups based on their BMI: I – BMI < 24.9 kg/m2; II – BMI 25–30 kg/m2; III – BMI > 30 kg/m2. Regression analysis was conducted to determine whether BMI was an independent predictor of early mortality after CABG. Results. The majority of the cohort could be categorized as overweight (49%) or obese (30%). There was no association between BMI and gender (p = 0.398). The overall early mortality was 2.15% (1.85% in the group I, 2.06% in the group II and 2.51% in the group III; p = 0.869). Univariate analysis showed that obesity cannot be regarded as an independent risk factor for early mortality following CABG (odds ratio 1.021, 95% confidence interval 0.910–1.145, p = 0.724). Duration of in-hospital period following the surgery was comparable within the BMI groups (p = 0.502). Conclusion. Compared to non-obese patients, overweight and obese individuals have similar early mortality rate following CABG. This study can substantiate the presence of obesity paradox only in terms that elevated BMI patients have comparable outcome with non-obese. Further research is needed to delineate potential underlying mechanisms that set off obesity to protective factor for coronary surgery.
Keywords: obesity; body mass index; myocardial revascularization; postoperative period; mortality